Usefulness of a CT‐guided hookwire marking in laparoscopic partial hepatectomy for hepatocellular carcinoma invisible on ultrasonography. Issue 1 (February 2017) - Monden, Kazuteru; Sadamori, Hiroshi; Hioki, Masayoshi; Nakano, Kanyu; Asami, Shinya; Ohno, Satoshi; Sasaki, Kyo; Ueki, Toru; Yabushita, Kazuhisa; Uka, Mayu; Hyodo, Tsuyoshi; Sakaguchi, Kousaku; et al.
Abstract: Introduction: The intra‐operative detection of hepatocellular carcinoma (HCC) by ultrasonography is indispensable for laparoscopic partial hepatectomy. However, it is occasionally difficult to localize an HCC on an ultrasound in chronic liver disease. Two cases of partial hepatectomy using hookwire marking under CT guidance are presented. Materials and Surgical Technique: The location of the HCC was identified by CT scan, and the puncture site was determined. A hookwire system, made of a stainless steel hook, was used to localize the HCC. The hookwire was placed percutaneously close to the HCC, and then the patient was taken to the operating room as soon as possible. After identification of the hookwire marker, the cutting line was determined on the liver surface to ensure a sufficient surgical margin in laparoscopic partial hepatectomy. Discussion: Two cases underwent these procedures with easy intra‐operative marking of the resection area. This technique facilitates safe laparoscopic partial hepatectomy for an HCC that is invisible on ultrasound.